‘I’m Scared to Death to Try It on My Own’: I-Poems and the complexities of religious housing support for people on the US sex offender registry - Leon, Chrysanthi; Buckridge, Maggie; Herdoíza, Michaela (Anti-Trafficking Review, 2023)
In the US, street-based sex workers and people convicted of sex offences are both ‘special populations’, often with additional conditions of community supervision. People convicted of sex offences experience a complicated mix of assistance and surveillance as they re-enter society post-conviction, including numerous restrictions on housing and employment. As a result, they are especially likely to experience homelessness upon release. This article uses I-Poems drawn from interviews with volunteers and professionals who navigate the obstacles to re-entry that govern people on the sex offender registry. We focus on people with religious affiliations (n=38) who provide urgent support during the re-entry process. I-poems are a feminist technique for analysing qualitative data that forefronts the voices of people not often heard and distils complex experiences into accessible narratives. While few in our study overtly exploited re-entering persons on the registry, most support was problematic in subtler ways: we found that re-entering registrants are asked to accept constrained choices involving labour, religious participation, and romantic and other personal relationships in order to receive assistance. Given the secondary stigma attached to work with people convicted of sex offences, and the obscurity within in which many of these religiously-affiliated programmes operate, I-Poems both humanise and reveal the complexities of coercion, religious calling, and supportive housing.